2023
DOI: 10.3390/livers3030033
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Non-Alcoholic Fatty Liver Disease and Visceral Fat Measured by Imaging-Based Body Composition Analysis: A Systematic Review

Ker Ming Seaw,
Christiani Jeyakumar Henry,
Xinyan Bi

Abstract: Imaging-based body composition analysis can quantify visceral fat, which is an important feature of lean non-alcoholic fatty liver disease (NAFLD) patients. This review assesses current evidence of the relationship between NAFLD, particularly hepatic steatosis, and visceral fat that is measured using imaging-based body composition analysis. PubMed Central and ScienceDirect were searched for studies that provided quantification of the relationship between NAFLD, hepatic steatosis and visceral fat. Twenty studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
1
0
0
Order By: Relevance
“…Adiposopathy is the combination of the accumulation of VAT and ectopic fat, inflammation, impaired adipose tissue expandability and adipogenesis, hypertrophy, and altered lipid metabolism [14]. In other studies, VATob has been shown to significantly increase the development of NAFLD [46], which is in accordance with our results. In fact, subjects with NAFLD were classified as VATob 2.1-times more than subjects without NAFLD, a difference greater than the observed for TAFAob and SATob.…”
Section: Plos Onesupporting
confidence: 91%
“…Adiposopathy is the combination of the accumulation of VAT and ectopic fat, inflammation, impaired adipose tissue expandability and adipogenesis, hypertrophy, and altered lipid metabolism [14]. In other studies, VATob has been shown to significantly increase the development of NAFLD [46], which is in accordance with our results. In fact, subjects with NAFLD were classified as VATob 2.1-times more than subjects without NAFLD, a difference greater than the observed for TAFAob and SATob.…”
Section: Plos Onesupporting
confidence: 91%